Dermoid sinus hos Rhodesian ridgeback - Bergman, Ingrid (SLU/Dept. of Animal Breeding and Genetics (until 231231), 2008)
Rhodesian ridgeback is a dog breed that originates from southern Africa. The characteristic ridge (a dorsal ridge where the hair grows in the opposite direction to the general coat) is shared with an Asian breed, Thai ridgeback. The origin and inheritance of the ridge has been examined and defined. The ridge-mutation is a duplication that contains four complete genes, FGF3, FGF4, FGF19 and ORAOV1 and the 3´-end of CCND1. The ridge is inherited as an autosomal, dominant trait and predisposes for Dermoid sinus (DS), a disease that develops during embryogenesis. The aim with this thesis is to look into the possibilities to reduce the number of dogs that gets affected by DS. DS belongs to a group of congenital malformations that is called Neural Tube Defects (NTD) and also can affect humans. Studies on humans have shown that addition of folic acid during pregnancy can reduce the risk of being affected by these malformations. According to an Australian study the same seems to apply to Rhodesian ridgebacks. Another suggestion to reduce the occurrence of DS in Rhodesian ridgebacks is to use ridgeless dogs in breeding. Dogs with ridge, which are homozygous for the mutation, are predisposed to DS, while ridgeless dogs never get affected by DS. By using a ridgeless dog there would not be any offspring homozygous for the mutation. Yet another suggestion is that a DNA-test should be developed to show the genotype of breeding dogs and exclude those with multiple copies of the duplication which may be at larger risk of producing offspring with DS.